IFRS for SMEs: Eine interessante Option für deutsche KMUs auf dem Gebiet der Konzernrechnungslegung? - Henselmann, Klaus; Roos, Benjamin (2009)
The paper analyzes whether the International Financial Reporting Standard for Small and Medium-sized Entities (IFRS for SMEs), published July 9, 2009, could be an interesting option for the consolidated financial statements of small and medium-sized entities (SMEs) in Germany. Background is the intention of the IASB to give SMEs an attractive alternative in accounting according to international standards. For this reason the analysis includes a comparison of the sections of the IFRS for SMEs concerning consolidated financial statement accounting with Full-IFRS and the modernized German GAAP. – Full-IFRS ; IFRS for SMEs ; Konzernrechnungslegung ; Kleine und Mittlere Unternehmen (KMUs) ; nicht-kapitalmarktorientierte Unternehmen ; Small and Medium-sized Entities